Exercises to improve trunk defenses in pioneer category boxers - Yonesky Velez Flores; Giraldo Machuat Santana; Modesta Moreno Iglesias; Francisco Boffil Hernández (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2020)
The practice of sports from an early age in Cuba is an objective of the maximum direction of the National Institute of Sports and Recreation (Inder in Spanish) where the integral preparation of the athlete is promoted by integrating all the components of the preparation. In the case of Boxing, the technical and tactical preparation constitutes an essential axis for the work with pioneer athletes. This work has the objective of elaborating a set of exercises that strategically contribute to the improvement of the work of the trunk defenses in school category boxers of Pinar del Río. In order to fulfill the objective, methods of theoretical and empirical level were used in the diagnosis, combined with statistical mathematicians, seeking to confirm the weaknesses and potentialities in the work of the trunk fenders in the pioneer category, to allow their improvement. In observations and interviews made with coaches, from the diagnosis to training sessions of the boxing team, category 11-12 pioneer, it was possible to corroborate that there are deficiencies in the work of the trunk defenses to counteract attacks with straight and cross blows to the face, specifically, since they do not have a variety of exercises for the performance of such work. All this allowed to verify the scientific problem and to plan a group of customized strategic exercises for the improvement of the trunk defense in the school category boxers, for the trainers in function to eradicate the deficiencies detected in the diagnosis, verifying its effectiveness from the specialists' criterion.